Interdiffusion under pressure in KBr-KCl single-crystals system - Kononenko, V.G.; Bogdanov, V.V.; Volosyuk, M.A.; Volosyuk, A.V. (Functional Materials, 2016)
Dependences of diffusion coefficients on pressure in the range from 1 to 6000 atm and at temperatures 450, 500, and 550°C in KBr and KCl single crystals were investigated by technique of sintering the compacts from KBr and KCl single crystals powder mixtures in the ratios providing 50 % KBr-KCl solid solution. Studying the kinetics of the solid solution formation was carried out by measuring the X-ray diffraction {200} intensity maxima depending on annealing time for the pure components. The obtained diffusion coefficient versus pressure dependences under the above-mentioned conditions indicate the observed diffusion coefficient decrease with increasing pressure (within this range) being caused by decreasing the equilibrium vacancies concentration under pressure.